Strategies for capacity building of extension personnel for using information and communication technologies - Chithra Gangadharan (Department of Agricultural Extension, College of Horticulture, 2015)
Information and Communication Technologies (ICTs) generally refer to expanding assembly of technologies that are used to handle information and aid communication. ICT in agriculture is an emerging field that involves application of innovative ways to use ICTs in the rural domain. The advancements in ICTs can be utilized for providing accurate, timely, relevant information and services to farmers, thereby facilitating an environment for more remunerative agriculture. The study intended to analyse the utilization pattern of ICTs, training needs and constraints faced by extension personnel, and to work out strategies for capacity building of extension personnel in using ICTs for agricultural development in Kerala. An ex-post facto research design was adopted. Five districts were selected from each agro climatic zone, and from each district, 30 Agricultural Officers were selected randomly, thus constituting a sample size of 150. It was observed that 66 per cent of the extension personnel were females, more than two-third of the extension personnel (71.33%) had only medium level of innovation proneness. High level of innovation proneness was noted among 14.66 per cent of the extension personnel. Three-fourth of the extension personnel (74.66%) did not receive trainings related to ICTs. With regard to the attitude towards ICTs, majority (86.66%) of the extension workers of all the districts were under medium category. Further, it is revealed that more than 85 per cent of the extension personnel had access towards ICT tools such as radio, television, land phone, mobile phone, computer, internet, e-mail, web based search engine and web-based agriculture information portals. The ICT tools with low extent of accessibility were Decision Support System, Video camera, Video conferencing and Kiosk, with less than 25 per cent. With regard to the utilization of ICT tools, the respondents were evenly distributed among the categories of very less frequent users, less frequent users, frequent users and most frequent users with 26 per cent each and most frequent users with 22 per cent only. More than 50 per cent of the extension officers mainly used various ICT tools for obtaining recent information to update their knowledge. Only less than 20 per cent of the extension professionals utilized majority of the ICT tools for offering advisory services and less than 10 per cent of the extension officials used various ICT tools for the purpose of teaching or training. More than 70 per cent of the respondents spent 1-5 hrs per week in using various ICT tools. The per cent of extension personnel who spent 5-10 hours per week for using various ICT tools ranged from 0.7 to 24.7.Very less per cent of the respondents spent 10-15 and above 15 hours per week on different ICT tools. ‘Sources of web based agricultural information’ was perceived as the most important training need related to knowledge level, with an index of 84.66, followed by ‘agricultural related websites (80) and basics of computer hardware and software (75.16). Regarding the skill level training needs, highest Training Need Index was obtained for ‘preparation of excel sheets and calculations’ (76) followed by ‘usage of agri portals’ with an index of 74.66 and ‘fertilizer recommendation systems’ (74.16). The major constraints faced by the extension personnel were lack of proper training facility with a mean score value of 9.48 followed by inadequate computer facility and poor technical knowhow and conducting trainings at inappropriate times with mean score of 8.32 each. Target specific training modules, hands on experience, well established infrastructure, adequate funds and personnel for repair and maintenance, computer based trainings and circulation of annual training calendars in advance are the suggested strategies for the capacity building of extension personnel of Kerala in using ICTs.